Fatigue Characteristic of Chopped Strand Mat/Polyester Composite - Astika, I Made (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009, 2012)
The application of composite as an alternatif material to substitute of metal has better properties than metal such as light, high elasticity, corrosion and fatigue resistance. Some components in its application are subjected to millions of varying stress cycles that initiated to fatigue failure such as crack, delamination and fracture. The strength of composite is influenced by construction, fiber type, orientation and fiber fraction. The objective of this experiment is to investigate the fatigue characteristic on SCM composite. Material composite to be used is glass fiber with chopped strand mat (CSM) as fiber and Yukalac 157 BQTN-EX with 1% hardener (Mexpox) as matrix. The mold process was built with hand lay-up. Fiber volume fractions in composite are 40, 32 and 24 %. The tests to be done on composite are fatigue and tensile test. The research show that the increasing of fiber fraction in composite affects increasing of fatigue life, endurance limit and tensile strength. Fatigue failure modes of composite are debonding, matrix cracking, delamination and fiber fracture.
Keywords: Composite, Chopped strand mat/polyeste , Fatigue characteristic.